2020
DOI: 10.1152/jn.00128.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol activation of vagal afferent neurons requires TRPA1

Abstract: Vagal afferent neurons abundantly express excitatory transient receptor potential (TRP) channels which strongly influence afferent signaling. Cannabinoids have been identified as direct agonists of TRP channels, including TRPA1 and TRPV1, suggesting exogenous cannabinoids may influence vagal signaling via TRP channel activation. The diverse therapeutic effects of electrical vagus nerve stimulation also result from administration of the non-psychotropic cannabinoid cannabidiol (CBD); however, the direct effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…One of its main contributions is the transduction of nociceptive stimuli in the primary afferent nerve endings during signal transmission in the dorsal horn spinal neurons, but it also participates in episodes of neurogenic inflammation [ 48 ]. In clinical medicine, this receptor is being studied due to its activation and therapeutic effect under the administration of cannabidiol (CBD) [ 50 ].…”
Section: Classification Of the Ionic Trp Channelsmentioning
confidence: 99%
“…One of its main contributions is the transduction of nociceptive stimuli in the primary afferent nerve endings during signal transmission in the dorsal horn spinal neurons, but it also participates in episodes of neurogenic inflammation [ 48 ]. In clinical medicine, this receptor is being studied due to its activation and therapeutic effect under the administration of cannabidiol (CBD) [ 50 ].…”
Section: Classification Of the Ionic Trp Channelsmentioning
confidence: 99%
“…Furthermore, recent studies have examined the crucial function of TRPA1 that plays an important role in mediating the excitatory effects of CBD in vagal neurons, and have shown that (1) CBD increases calcium intracellular from an external source and induces depolarizations; (2) this responsiveness requires TRPA1, but is improved by expression of TRPV1. [33] Abn-CBD is a synthetic CBD regioisomer that has not seen noticeable behavioral consequences in preliminary studies. [34][35][36] In comparison to most other cannabinoids, these causes vasodilator effects reduce blood pressure, and stimulates cell differentiation, cell proliferation, and mitogen-activated protein kinase activation in microglia, but without any psychoactive effects.…”
Section: The Cannabinoid Systemmentioning
confidence: 99%
“…[105][106][107] Although prompt reperfusion restores oxygen and substrates needed for aerobic ATP generation and optimizes extracellular pH by cleaning H+ accumulated, reperfusion itself tends to have adverse effects. Furthermore, recent studies have examined the crucial function of TRPA1 that plays an important role in mediating the excitatory effects of Abn-CBD in vagal neurons, and have shown that (1) Abn-CBD increases calcium intracellular from an external source and induces depolarizations; (2) this responsiveness requires TRPA1, but is improved by expression of TRPV1 [33] that contribute in further enhancing reflex towards adrenergic flux may increase the responsiveness towards Gαs protein-mediated cardiac depolarization. In this way, avoidance of KATP opening has been described as a cardioprotection paradigm for heart hypoxia-ischemic injury in cardiovascular compromise preterm infants.…”
Section: Abn-cbd Directed Cardiovascular Protection Involving Dysfunctional B -Adrenergic and Katp Activity In Cardiovascular Compromisedmentioning
confidence: 99%
See 1 more Smart Citation
“…Marichal-Cancino et al 61 identified an associated effect of GPR55 as CBD blocked an LPI inhibition of noradrenalines-related vasopressor responses, which indicated that this receptor could play a role in the outcomes of CBD. Recently, however, studies have investigated the key role of transient receptor potential ankyrin1 which is an essential factor in facilitating the excitatory effects in vagal neurons of CBD, and have shown that CBD raises the intracellular calcium from external sources to cause depolarizations 62 (Figure 2).…”
Section: Biology Of Abnormal Cannabidiols System In Cardiovascular Protectionmentioning
confidence: 99%